Accounting for Non-Financial Assets in the Public Finance Management System in Ukraine during the Conflict - TSIATKOVSKA, Olena; PRYMACHENKO, Olena; LEZHNENKO, Liudmyla; FESHCHENKO, Yevheniya; MYKHALSKA, Olena (Theoretical and Practical Research in Economic Fields, 2024)
The relevance of the study lies in the fact that accounting and effective management of non-financial assets in times of conflict is strategically important for ensuring sustainability, economic recovery, and resource security of the state. The purpose of the study is to analyse the features of accounting for non-financial assets in the management of public finances in the war and post-war period. Among the methods used were the analytical, statistical, functional, system analysis, deduction, synthesis, and comparison. This study is devoted to the investigation of methods for assessing and reclassifying non-financial assets of state institutions in the context of military conflict, in particular, considering the aggression of Russia and the temporary occupation of the territory of Ukraine. The main criteria related to restricted access to non-financial assets were identified, and an algorithm for reclassification in case of loss or restricted access to them was proposed. Considering the criteria, a recommendation system has been developed for recognising and reclassifying non-financial assets in military conditions. The study emphasises the need to regulate this issue in the legal field, in particular, by making changes to the relevant regulatory documents that would consider the specifics of managing and evaluating non-financial assets during the war period. These changes include reclassification procedures and rules for recording such assets in financial statements, considering their real value and restricted access status. The practical significance of this study is to develop specific recommendations and procedures for reclassification of non-financial assets of state institutions in the context of military conflict, which will improve the efficiency of management and reflection of their value in conditions of limited access.